The Role of digital supervision in enhancing teacher performance in Indonesian secondary education - Sapwan, Andika; Meirawan, Danny; Saton, Djam’an; Sutarsih, Cicih (Indonesian Research Journal in Education |IRJE|, 2025)
This study investigates how digital supervision improves teacher performance in Indonesian secondary schools. Eight SMA Labschool Universitas Syiah Kuala participants, including principals, supervisors, and teachers were interviewed using a qualitative method. NVivo 12 was used to analyze word frequencies, themes, and relationships. Findings reveal that digital supervision enhances teacher performance by improving technological and pedagogical competence, fostering creativity, and increasing administrative efficiency—tools like Google Classroom and Zoom support real-time feedback and collaboration. However, limited infrastructure, weak Internet connectivity, and digital skill gaps persist. The study concludes that digital supervision significantly improves teaching quality when backed by sufficient training and facilities. It recommends targeted digital training and improved infrastructure to optimize implementation.